2014
DOI: 10.1021/ef5005896
|View full text |Cite
|
Sign up to set email alerts
|

Effective Activation Energies of Lignocellulosic Biomass Pyrolysis

Abstract: Eight different three-parallel distributed activation energy model (DAEM) reaction model processes, which were used to describe the pyrolysis of eight lignocellulosic biomass samples very well, were analyzed by means of the Cai−Chen iterative linear integral isoconversional method. The activation energies obtained from the isoconversional method were independent of the heating rate, which indicated that the isoconversional analysis was valid for the pyrolysis of lignocellulosic biomass. The resulting effective… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
35
0
1

Year Published

2014
2014
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 79 publications
(38 citation statements)
references
References 41 publications
2
35
0
1
Order By: Relevance
“…It can also be observed that the thermal decomposition profiles of all the biomass samples were analogous irrespective of the pre-treatments. The thermal degradations were also independent of the heating rates employed implying that the isoconversion kinetic analysis was valid for the thermal degradation of the D. fir and H. pop biomass samples (Wu et al, 2014). Akin to the mass loss curves of the untreated samples, the pre-treatment curves were asymmetrical and moved up with an increase in the heating rate.…”
Section: Tgamentioning
confidence: 86%
See 1 more Smart Citation
“…It can also be observed that the thermal decomposition profiles of all the biomass samples were analogous irrespective of the pre-treatments. The thermal degradations were also independent of the heating rates employed implying that the isoconversion kinetic analysis was valid for the thermal degradation of the D. fir and H. pop biomass samples (Wu et al, 2014). Akin to the mass loss curves of the untreated samples, the pre-treatment curves were asymmetrical and moved up with an increase in the heating rate.…”
Section: Tgamentioning
confidence: 86%
“…The variation of activation energy with conversion was more pronounced in D. fir samples compared to the H. pop. This type of variation might be due to the overlapped thermal decomposition reaction of the bio-polymers (Wu et al, 2014). The activation energies (ASTM method) for the D. fir samples followed the order: salt pre-treated (259.3 kJ/mol) N acid pre-treated (203 kJ/mol) N HWT (205.5 kJ/mol) N Torrefied (188.3 kJ/mol) N untreated (186.6 kJ/mol).…”
Section: Tgamentioning
confidence: 99%
“…In the literature, the pyrolysis kinetics and properties of some "pure" materials such as wood [1][2][3][4][5], polyurethane foams [6,7] and PMMA [8] are most studied. Composite materials used in buildings such as medium density fibreboard (MDF) are rarely studied due to its complex physiochemical properties.…”
Section: Introductionmentioning
confidence: 99%
“…The model used in this work was originally proposed by Koufopanos et al [18]. This model assumes that (1) lignocellulosic biomass contains cellulose, hemicellulose, lignin, and non-CHL components; (2) there is no interaction between these biomass components; (3) cellulose, hemicellulose, and lignin contribute to the formation of volatile products (including bio-oil and syngas) and charcoal via competing reactions; and (4) non-CHL components do not decompose.…”
Section: Kinetic Modelmentioning
confidence: 99%
“…The major components of lignocellulosic biomass are cellulose, hemicellulose, and lignin [2]. Pyrolysis can convert lignocellulosic biomass into charcoal and volatile products (including bio-oil and syngas) [3,4].…”
Section: Introductionmentioning
confidence: 99%